Kepemimpinan Transformasional Kepala Madrasah Dalam Implementasi Kurikulum Merdeka - VikaSari, Asri Yuni; Fauzi, Anis; Bahaf, Abdul Muin; Gunawan, Agus; Priatna, Suherman (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
Leaders have a key role in dealing with curriculum changes. They are responsible for identifying new needs and motivating team members through transformational leadership. This research uses qualitative methods with library research, using primary data from documents and secondary data from national/international journals with the keywords